ANALYSIS OF FINANCIAL PERFOMANCE AT PT. KIMIA FARMA TBK BEFORE AND DURING THE COVID-19 PANDEMIC - Kamaluddin, Nurhadi; Insani, Ade Ilma (Politeknik Negeri Semarang, 2024)
During the Covid-19 pandemic, there was a decrease in GDP by 2.07%. As a result, many company sectors experienced a contraction in economic growth, but some company sectors actually experienced an increase in productivity, one of which was the health sector. This study aims to determine the differences in the financial performance of PT Kimia Farma, Tbk before and during the Covid-19 pandemic in terms of Current Ratio, Quick Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Net Profit Margin, Return on Equity, Total Assets Turnover, and Fixed Assets Turnover. With quantitative descriptive research methods and sample population using the financial statements of PT Kimia Farma, Tbk for the period 2017-2022. With data analysis techniques, namely financial ratio analysis, normality test, Paired Samples T-test, and processed using SPSS v.21. The results of the study concluded that based on the Paired Samples T-test test, the results showed the acquisition of a Sig value. (2-tailed) of (0.549)>Î± (0.05) for Current Ratio, (0.269)>Î± (0.05) for Quick Ratio, (0.358)>Î± (0.05) for Debt to Asset Ratio, (0.349)>Î± (0.05) for Debt to Equity Ratio, (0.283)>Î±(0.05) for Net Profit Margin, (0.779)>Î±(0.05) for Return on Equity, (0.343)>Î±(0.05) for Total Assets Turnover, and (0.218)>Î±(0.05) for Fixed Assets Turnover. So it can be concluded that there is no significant difference in financial performance before and during the Covid-19 pandemic.